A method for preparing selenolized carbon nanotube natural rubber composite material
By selenizing the carbon nanotubes, they form a composite material that is uniformly dispersed and efficiently combined with natural rubber, the problems of poor dispersion and insufficient interface binding force of carbon nanotubes in the rubber matrix are solved, and the composite is significantly improved Mechanical properties of materials.
Patent Information
- Application Number
- CN202411157876.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-22
AI Technical Summary
The poor dispersion of carbon nanotubes in the rubber matrix and insufficient interface binding force lead to the inadequate enhancement effect being fully exerted, and may even lead to a degradation of the performance of rubber products.
Selenoxified carbon nanotubes were prepared by selenoxizing the aminocarbon nanotubes with selenoxane heterocyclic rings, and reacted with natural rubber rubber solution under a protective atmosphere to form a selenoxane carbon nanotube natural rubber composite material.
The uniform dispersion and efficient combination of carbon nanotubes in natural rubber are achieved, which significantly improves the mechanical properties and reinforcement effect of composite materials.
Smart Images

Figure CN118812929B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber composite materials, and in particular to a method for preparing a selenolated carbon nanotube natural rubber composite material. Background Art
[0002] Carbon nanotubes, or CNTs for short, have great potential for application in the fields of reinforced composite materials, electronic devices, thermal management materials, etc., due to their unique structural characteristics, such as extremely high aspect ratio, excellent mechanical strength, good electrical and thermal conductivity, etc. In the rubber industry in particular, carbon nanotubes are regarded as a very promising reinforcing filler. Studies have shown that adding a small amount of carbon nanotubes to rubber can produce a strong reinforcing effect, which is much stronger than traditional fillers such as carbon black. Moreover, when carbon nanotubes are dispersed in polymers, the electrical and thermal conductivity of the material can be improved. Therefore, carbon nanotubes are expected to replace traditional fillers such as carbon black and achieve a significant improvement in the performance of rubber products.
[0003] However, despite the many advantages of carbon nanotubes, their practical application in rubber matrices faces severe challenges, mainly focusing on two major issues: dispersibility and interfacial bonding strength. First, due to the extremely high aspect ratio of carbon nanotubes and the strong π-π interaction between carbon nanotube molecules, these characteristics cause carbon nanotubes to easily agglomerate in the rubber matrix, making it difficult to achieve uniform dispersion through traditional rubber dry mixing processes. This uneven dispersion state not only fails to fully exert the reinforcing effect of carbon nanotubes, but may also cause the performance of rubber products to deteriorate due to the formation of stress concentration points due to agglomerates.
[0004] In addition, the surface of carbon nanotubes is smooth and chemically inert, lacking active sites for forming effective chemical bonds with the rubber matrix, which makes the interfacial bonding between carbon nanotubes and the rubber matrix weak. The lack of interfacial bonding not only limits the reinforcing effect of carbon nanotubes in the rubber matrix, but may also cause the rubber products to fail due to interfacial debonding during use. Summary of the invention
[0005] In order to solve the problems of dispersibility and interface bonding strength of carbon nanotubes in a rubber matrix, the present invention aims to provide a method for preparing a selenolized carbon nanotube natural rubber composite material.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] The present invention provides a method for preparing a selenolized carbon nanotube natural rubber composite material, comprising the following steps:
[0008] The amino carbon nanotubes and the selenium-containing aliphatic heterocycles are subjected to a selenolation reaction to prepare selenolated carbon nanotubes;
[0009] Under a protective atmosphere, the selenolated carbon nanotubes and natural rubber solution are reacted under the action of an oxidant to prepare selenolated carbon nanotube natural rubber;
[0010] The selenol carbon nanotube natural rubber is mixed with a crosslinking agent, an accelerator and a reinforcing filler and vulcanized to prepare a selenol carbon nanotube natural rubber composite material.
[0011] The present invention performs surface modification on carbon nanotubes and introduces selenol groups having good compatibility with natural rubber, so that the modified carbon nanotubes can be evenly dispersed in the natural rubber and play a good reinforcing role.
[0012] Preferably, the selenium-containing aliphatic heterocycle is γ-selenobutyrolactone. The structural formula of γ-selenobutyrolactone is
[0013] Preferably, the molar ratio of the aminated carbon nanotubes to the selenium-containing aliphatic heterocycle is 0.02-0.4:0.02-0.4.
[0014] Preferably, the amino-modified carbon nanotubes are prepared by the following method:
[0015] The carboxylated carbon nanotubes are subjected to amination modification under the action of an acyl chloride reagent and an amination reagent to prepare the amination carbon nanotubes; the acyl chloride reagent is thionyl chloride; the amination reagent is ethylenediamine.
[0016] Preferably, the amino-modified carbon nanotubes are prepared by the following method:
[0017] The carboxylated carbon nanotubes, acyl chloride reagent and organic solvent are mixed, stirred and reacted at 50°C to 70°C. After the reaction is completed, the acyl chloride reagent is evaporated to remove the acyl chloride reagent, and then an amination reagent is added, stirred and refluxed to prepare the amination carbon nanotubes.
[0018] Preferably, the usage ratio of the carboxylated carbon nanotubes, the acyl chloride reagent, and the amination reagent is 200 mg: 20 mL: 0.06 mg.
[0019] Preferably, the mass ratio of selenolized carbon nanotubes to natural rubber solution is 0.05-0.1:100.
[0020] Preferably, the oxidant is a hydrogen peroxide solution or a chlorine peroxide solution; the mass ratio of the natural rubber glue to the oxidant is 100:0.09-0.24; and the mass percentage of the oxidant is 10wt%.
[0021] Preferably, the crosslinking agent is sulfur; the accelerator is zinc oxide and N-cyclohexyl-2-benzothiazole sulfenamide; the reinforcing filler is carbon black;
[0022] The mass ratio of zinc oxide to N-cyclohexyl-2-benzothiazole sulfenamide is 4 to 6:1;
[0023] The mass ratio of selenolized carbon nanotube natural rubber, crosslinking agent, accelerator and reinforcing filler is 100:2-3:5-7:30-80.
[0024] Preferably, the mixing temperature is 130-150° C.; the vulcanization temperature is 150° C.; and the vulcanization time is 20 min to 60 min.
[0025] Beneficial effects of the present invention:
[0026] 1. The present invention mainly utilizes selenium-containing aliphatic heterocycles to perform selenol modification on amino carbon nanotubes, and utilizes the selenol groups to react with double bonds in natural rubber, so that the carbon nanotubes are uniformly grafted onto the natural rubber, thereby improving the dispersibility of the carbon nanotubes and the natural rubber, and at the same time improving the mechanical properties of the natural rubber composite material, thereby playing a better reinforcing role.
[0027] 2. The method of the present invention modifies carbon nanotubes by selenolization so that the modified carbon nanotubes can be more evenly dispersed in natural rubber. The preparation method is simple and easy to operate, and has great potential application value in the industrial field. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the selenolized carbon nanotube natural rubber composite material prepared in Example 1 at 10 μm.
[0029] Figure 2 This is a scanning electron microscope image of the selenolized carbon nanotube natural rubber composite material prepared in Example 1 at 5 μm.
[0030] Figure 3 This is a scanning electron microscope image of the selenolized carbon nanotube natural rubber composite material prepared in Example 1 at 2 μm.
[0031] Figure 4 This is a scanning electron microscope image of the amino carbon nanotube natural rubber composite material prepared in Comparative Example 2 at 2 μm. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0034] The technical solution of the present invention is described in detail below through specific examples. In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0035] In the following embodiments, CNTs is carbon nanotube; CNTs-COOH is carboxylated carbon nanotube; CNTs-OH is hydroxylated carbon nanotube; DCC is dicyclohexylcarbodiimide; DMAP is 4-dimethylaminopyridine; PAA is acrylic acid; DMF is N,N-dimethylformamide; SOCl2 is thionyl chloride; ZnO is zinc oxide; promoter CZ is N-cyclohexyl-2-benzothiazolesulfonamide, Shanghai Shuangguan Chemical Co., Ltd.
[0036] In the following embodiments, carbon black is produced by Cabot Chemical (Tianjin) Co., Ltd., and the product model is N330.
[0037] In the following embodiments, the Chinese name of the Schlenk tube is reaction tube, and the material is high borosilicate glass.
[0038] In the following embodiments, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere, preferably a nitrogen atmosphere.
[0039] In the following examples, the mass fraction of concentrated sulfuric acid is about 98.3%, the mass fraction of concentrated nitric acid is about 68%, and the purity of selenium powder is about 99.99% (wt).
[0040] In the following examples, the toluene solution of 4-chlorobutyryl chloride is obtained by dissolving 4-chlorobutyryl chloride in a toluene solvent, wherein the usage ratio of 4-chlorobutyryl chloride to toluene is 7 g:100 mL.
[0041] In the following embodiments, the structural formula of γ-selenobutyrolactone is
[0042] In the following examples, the natural rubber solution was purchased from Hainan Natural Rubber Industry Group Co., Ltd., and the solid content was 60 wt%.
[0043] In the following embodiments, during the preparation of the selenolized carbon nanotube natural rubber composite material, the mixing temperature was controlled at 130-150°C to meet the requirements. For the convenience of comparison, the mixing temperature of the following embodiments was selected to be 140°C.
[0044] Example 1
[0045] A method for preparing a selenolized carbon nanotube natural rubber composite material comprises the following steps:
[0046] Step 1, preparation of carboxylated carbon nanotubes:
[0047] 1.00 g of CNTs was weighed and dispersed in a mixture of 20 mL of concentrated sulfuric acid and 20 mL of concentrated nitric acid, ultrasonically dispersed for 30 min, and then subjected to thermal reflux reaction at 140 ° C for 60 min. The product was washed with distilled water several times until neutral, filtered, and dried to obtain hydroxylated carbon nanotubes, recorded as CNTs-OH.
[0048] 50 mg of CNTs-OH was weighed and placed in 40 mL of DMF solvent, and ultrasonic dispersion was performed at an ultrasonic frequency of 100 Hz for 30 min to obtain a uniformly dispersed CNTs-OH suspension.
[0049] 0.2 g DCC, 0.015 g DMAP and 0.75 g acrylic acid were weighed, dissolved in 40 mL DMF solvent, and then added to the CNTs-OH suspension, and reacted at 85°C for 24 h under inert atmosphere. After washing, filtering and drying, carboxylated carbon nanotubes were obtained, which were recorded as CNTs-COOH.
[0050] Step 2, preparation of amino-modified carbon nanotubes:
[0051] CNTs-COOH, SOCl2, and DMF were mixed in a ratio of 200 mg: 20 mL: 1 mL, ultrasonicated at 50 ° C for 2 h, and then magnetically stirred at 70 ° C for 12 h. After the reaction, the system was heated to 120 ° C, most of the SOCl2 was evaporated, vacuum dried, and then added to excess ethylenediamine, where the mass ratio of CNTs-COOH to ethylenediamine was 200 mg: 0.06 mg. Then heated and stirred under reflux at 120 ° C oil bath for 24 h, cooled, filtered under reduced pressure with medium-speed qualitative filter paper, washed with anhydrous ethanol 5 to 8 times, and the product was vacuum dried at 50 ° C to obtain amino carbon nanotubes.
[0052] Step 3, preparation of γ-selenobutyrolactone:
[0053] In a 2L three-necked flask, add 32g of selenium powder and 500mL of deionized water, pass argon for 15min to remove oxygen, and obtain a reaction solution. Dissolve 30.5g of sodium borohydride in 200mL of deionized water, and slowly dropwise add it to the reaction solution under 0℃ ice-water bath conditions and argon atmosphere. After the dropwise addition is completed, vigorously stir at room temperature for 2h to obtain a silver-gray solution.
[0054] Under an argon atmosphere, add 5.12g of tetrabutylammonium hydrogen sulfate as a phase transfer catalyst, slowly drip 800mL of a toluene solution of 4-chlorobutyryl chloride, and after the dropwise addition, vigorously stir overnight at room temperature for 18h. Add 13.44g of a 5% sodium bicarbonate aqueous solution to neutralize the reaction solution and adjust the pH value of the reaction solution to 7.0-7.5. Filter to remove the solid residue, separate the filtrate to obtain an aqueous phase and an organic phase, and extract the aqueous phase three times with ethyl acetate. Combine the organic phases, add anhydrous sodium sulfate to dry, filter, and rotary evaporation to remove the solvent. Then, distill the residue under reduced pressure to obtain a colorless transparent liquid, i.e., γ-selenobutyrolactone.
[0055] Step 4, preparation of selenolized carbon nanotubes:
[0056] In a 10 mL Schlenk tube equipped with a magnetic stirring bar, 0.30 mmol of γ-selenobutyrolactone, 0.3 mL of DMF and 0.30 mmol of amino carbon nanotubes were added. After stirring the reaction at 100 ° C for 10 minutes, the reaction mixture was cooled to room temperature and then dripped into 200 mL of methanol through a cotton filter. The obtained precipitate was filtered and vacuum dried at 50 ° C to obtain selenol carbon nanotubes.
[0057] Step 5, preparation of selenolized carbon nanotube natural rubber:
[0058] 0.06 g of selenolated carbon nanotubes was added to 100 g of natural rubber solution with a solid content of 60 wt%, and 0.12 g of a 10 wt% hydrogen peroxide solution was added. After stirring for 0.6 h under nitrogen protection, the dispersion was dried at 60° C. to obtain selenolated carbon nanotube natural rubber.
[0059] Step 6, preparation of selenolized carbon nanotube natural rubber composite material:
[0060] 100 g of selenolized carbon nanotube natural rubber was placed in an open mill, 5 g of ZnO, 3 g of sulfur, 1 g of accelerator CZ and 50 g of carbon black were added, mixed at 140° C. for 0.5 h, placed in a flat vulcanizer, and kept at a constant temperature of 150° C. for 30 min to obtain a selenolized carbon nanotube natural rubber composite material.
[0061] Example 2
[0062] A method for preparing a selenolized carbon nanotube natural rubber composite material comprises the following steps:
[0063] Step 1, preparation of carboxylated carbon nanotubes:
[0064] 1.50 g of CNTs were weighed and dispersed in a mixture of 20 mL of concentrated sulfuric acid and 20 mL of concentrated nitric acid, ultrasonically dispersed for 30 min, and then subjected to thermal reflux reaction at 140 ° C for 60 min. The product was washed with distilled water several times until neutral, filtered, and dried to obtain hydroxylated carbon nanotubes, recorded as CNTs-OH.
[0065] 60 mg of CNTs-OH was weighed and placed in 50 mL of DMF solvent, and ultrasonic dispersion was performed at an ultrasonic frequency of 100 Hz for 30 min to obtain a uniformly dispersed CNTs-OH suspension.
[0066] 0.3 g DCC, 0.0225 g DMAP and 0.5 g acrylic acid were weighed and dissolved in 50 mL DMF solvent, then added to the CNTs-OH suspension, and reacted at 85°C for 24 h under inert atmosphere. After washing, filtering and drying, carboxylated carbon nanotubes were obtained, which were recorded as CNTs-COOH.
[0067] Step 2, preparation of amino-modified carbon nanotubes:
[0068] CNTs-COOH, SOCl2, and DMF were mixed in a ratio of 200 mg: 20 mL: 1 mL, ultrasonicated at 50 ° C for 2 h, and then magnetically stirred at 70 ° C for 12 h. After the reaction, the system was heated to 120 ° C, most of the SOCl2 was evaporated, vacuum dried, and then added to excess ethylenediamine, where the mass ratio of CNTs-COOH to ethylenediamine was 200 mg: 0.06 mg. Then heated and stirred in an oil bath at 120 ° C for 24 h, cooled, filtered under reduced pressure with medium-speed qualitative filter paper, washed with anhydrous ethanol 5 to 8 times, and the product was vacuum dried at 50 ° C to obtain amino carbon nanotubes.
[0069] Step 3, preparation of γ-selenobutyrolactone:
[0070] In a 2L three-necked flask, add 32g of selenium powder and 500mL of deionized water, pass argon for 15min to remove oxygen, and obtain a reaction solution. Dissolve 30.5g of sodium borohydride in 200mL of deionized water, and slowly dropwise add it to the reaction solution under 0℃ ice-water bath conditions and argon atmosphere. After the dropwise addition is completed, vigorously stir at room temperature for 2h to obtain a silver-gray solution.
[0071] Under an argon atmosphere, add 5.12g of tetrabutylammonium hydrogen sulfate as a phase transfer catalyst, slowly drip 800mL of a toluene solution of 4-chlorobutyryl chloride, and after the dropwise addition, vigorously stir overnight at room temperature for 18h. Add 13.44g of a 5% sodium bicarbonate aqueous solution to neutralize the reaction solution and adjust the pH value of the reaction solution to 7.0-7.5. Filter to remove the solid residue, separate the filtrate to obtain an aqueous phase and an organic phase, and extract the aqueous phase three times with ethyl acetate. Combine the organic phases, add anhydrous sodium sulfate to dry, filter, and rotary evaporation to remove the solvent. Then, distill the residue under reduced pressure to obtain a colorless transparent liquid, i.e., γ-selenobutyrolactone.
[0072] Step 4, preparation of selenolized carbon nanotubes:
[0073] In a 10 mL Schlenk tube equipped with a magnetic stirring bar, 0.30 mmol of γ-selenobutyrolactone, 0.3 mL of DMF and 0.30 mmol of amino carbon nanotubes were added. After stirring the reaction at 100 ° C for 10 minutes, the reaction mixture was cooled to room temperature and then dripped into 200 mL of methanol through a cotton filter. The obtained precipitate was filtered and vacuum dried at 50 ° C to obtain selenol carbon nanotubes.
[0074] Step 5, preparation of selenolized carbon nanotube natural rubber:
[0075] 0.06 g of selenolated carbon nanotubes was added to 100 g of natural rubber solution with a solid content of 60 wt%, and 0.24 g of chlorine peroxide with a mass percentage concentration of 10 wt% was added. After stirring for 0.6 h under nitrogen protection, the dispersion was dried at 60° C. to obtain selenolated carbon nanotube natural rubber.
[0076] Step 6, preparation of selenolized carbon nanotube natural rubber composite material:
[0077] 100 g of selenolized carbon nanotube natural rubber was placed in an open mill, 5 g of ZnO, 3 g of sulfur, 1 g of accelerator CZ and 40 g of carbon black were added, mixed at 140° C. for 0.5 h, placed in a flat vulcanizer, and kept at a constant temperature of 150° C. for 20 min to obtain a selenolized carbon nanotube natural rubber composite material.
[0078] Example 3
[0079] A method for preparing a selenolized carbon nanotube natural rubber composite material comprises the following steps:
[0080] Step 1, preparation of carboxylated carbon nanotubes:
[0081] 0.5 g of CNTs were weighed and dispersed in a mixture of 10 mL of concentrated sulfuric acid and 10 mL of concentrated nitric acid, ultrasonically dispersed for 30 min, and then subjected to thermal reflux reaction at 130 ° C for 70 min. The product was washed with distilled water several times until neutral, filtered, and dried to obtain hydroxylated carbon nanotubes, recorded as CNTs-OH.
[0082] 40 mg of CNTs-OH was weighed and placed in 30 mL of DMF solvent, and ultrasonic dispersion was performed at an ultrasonic frequency of 100 Hz for 20 min to obtain a uniformly dispersed CNTs-OH suspension.
[0083] 0.1 g DCC, 0.010 g DMAP and 0.4 g acrylic acid were weighed and dissolved in 30 mL DMF solvent, then added to the CNTs-OH suspension and reacted at 85°C for 24 h under inert atmosphere. After washing, filtering and drying, carboxylated carbon nanotubes were obtained, which were recorded as CNTs-COOH.
[0084] Step 2, preparation of amino-modified carbon nanotubes:
[0085] CNTs-COOH, SOCl2, and DMF were mixed in a ratio of 200 mg: 20 mL: 1 mL, and ultrasonicated at 50 ° C for 1 h to 3 h, and then magnetically stirred at 70 ° C for 10 h to 14 h. After the reaction, the system was heated to 120 ° C, most of the SOCl2 was evaporated, vacuum dried, and then added to excess ethylenediamine, where the mass ratio of CNTs-COOH to ethylenediamine was 200 mg: 0.06 mg. Then heated and stirred in an oil bath at 120 ° C for 24 h, cooled, filtered under reduced pressure with medium-speed qualitative filter paper, washed with anhydrous ethanol 5 to 8 times, and the product was vacuum dried at 50 ° C to obtain amino carbon nanotubes.
[0086] Step 3, preparation of γ-selenobutyrolactone:
[0087] In a 2L three-necked flask, add 32g of selenium powder and 500mL of deionized water, pass argon for 15min to remove oxygen, and obtain a reaction solution. Dissolve 30.5g of sodium borohydride in 200mL of deionized water, and slowly dropwise add it to the reaction solution under 0℃ ice-water bath conditions and argon atmosphere. After the dropwise addition is completed, vigorously stir at room temperature for 2h to obtain a silver-gray solution.
[0088] Under an argon atmosphere, add 5.12g of tetrabutylammonium hydrogen sulfate as a phase transfer catalyst, slowly drip 800mL of a toluene solution of 4-chlorobutyryl chloride, and after the dropwise addition, vigorously stir overnight at room temperature for 18h. Add 13.44g of a 5% sodium bicarbonate aqueous solution to neutralize the reaction solution and adjust the pH value of the reaction solution to 7.0-7.5. Filter to remove the solid residue, separate the filtrate to obtain an aqueous phase and an organic phase, and extract the aqueous phase three times with ethyl acetate. Combine the organic phases, add anhydrous sodium sulfate to dry, filter, and rotary evaporation to remove the solvent. Then, distill the residue under reduced pressure to obtain a colorless transparent liquid, i.e., γ-selenobutyrolactone.
[0089] Step 4, preparation of selenolized carbon nanotubes:
[0090] In a 10 mL Schlenk tube equipped with a magnetic stirring bar, 0.15 mmol of γ-selenobutyrolactone was added. 0.3 mL of DMF and 0.15 mmol of amino carbon nanotubes were added. After stirring the reaction at 100 ° C for 10 minutes, the reaction mixture was cooled to room temperature and then dripped into 300 mL of methanol through a cotton filter. The obtained precipitate was filtered and vacuum dried at 50 ° C to obtain selenol carbon nanotubes.
[0091] Step 5, preparation of selenolized carbon nanotube natural rubber:
[0092] 0.05 g of selenolated carbon nanotubes was added to 100 g of natural rubber solution with a solid content of 60 wt%, and 0.09 g of 10 wt% hydrogen peroxide was added. After stirring for 0.5 h under nitrogen protection, the dispersion was dried at 60° C. to obtain selenolated carbon nanotube natural rubber.
[0093] Step 6, preparation of selenolized carbon nanotube natural rubber composite material:
[0094] 100 g of selenolized carbon nanotube natural rubber was placed in an open mill, 4 g of ZnO, 2 g of sulfur, 1 g of accelerator CZ and 30 g of carbon black were added, mixed at 140° C. for 0.5 h, placed in a flat vulcanizer, and kept at a constant temperature of 150° C. for 20 min to obtain a selenolized carbon nanotube natural rubber composite material.
[0095] Example 4
[0096] A method for preparing a selenolized carbon nanotube natural rubber composite material comprises the following steps:
[0097] Step 1, preparation of carboxylated carbon nanotubes:
[0098] Weigh 2g of CNTs and disperse them in a mixture of 30mL of concentrated sulfuric acid and 30mL of concentrated nitric acid, ultrasonically disperse for 30min, and then perform a thermal reflux reaction at 150°C for 50min. The product is washed with distilled water several times until neutral, filtered, and dried to obtain hydroxylated carbon nanotubes, which are recorded as CNTs-OH.
[0099] 60 mg of CNTs-OH was weighed and placed in 50 mL of DMF solvent, and ultrasonic dispersion was performed at an ultrasonic frequency of 100 Hz for 40 min to obtain a uniformly dispersed CNTs-OH suspension.
[0100] 0.3 g DCC, 0.03 g DMAP and 0.9 g acrylic acid were weighed and dissolved in 50 mL DMF solvent, then added to the CNTs-OH suspension, and reacted at 85°C for 24 h under inert atmosphere. After washing, filtering and drying, carboxylated carbon nanotubes were obtained, which were recorded as CNTs-COOH.
[0101] Step 2, preparation of amino-modified carbon nanotubes:
[0102] CNTs-COOH, SOCl2, and DMF were mixed in a ratio of 200 mg: 20 mL: 1 mL, and ultrasonicated at 50 ° C for 1 h to 3 h, and then magnetically stirred at 70 ° C for 12 h to 13 h. After the reaction, the system was heated to 120 ° C, most of the SOCl2 was evaporated, vacuum dried, and then added to excess ethylenediamine, where the mass ratio of CNTs-COOH to ethylenediamine was 200 mg: 0.06 mg. Then heated and stirred in an oil bath at 120 ° C for 24 h, cooled, filtered under reduced pressure with medium-speed qualitative filter paper, washed with anhydrous ethanol 5 to 8 times, and the product was vacuum dried at 50 ° C to obtain amino carbon nanotubes.
[0103] Step 3, preparation of γ-selenobutyrolactone:
[0104] In a 2L three-necked flask, add 32g of selenium powder and 500mL of deionized water, pass argon for 15min to remove oxygen, and obtain a reaction solution. Dissolve 30.5g of sodium borohydride in 200mL of deionized water, and slowly dropwise add it to the reaction solution under 0℃ ice-water bath conditions and argon atmosphere. After the dropwise addition is completed, vigorously stir at room temperature for 2h to obtain a silver-gray solution.
[0105] Under an argon atmosphere, add 5.12g of tetrabutylammonium hydrogen sulfate as a phase transfer catalyst, slowly drip 800mL of a toluene solution of 4-chlorobutyryl chloride, and after the dropwise addition, vigorously stir overnight at room temperature for 18h. Add 13.44g of a 5% sodium bicarbonate aqueous solution to neutralize the reaction solution and adjust the pH value of the reaction solution to 7.0-7.5. Filter to remove the solid residue, separate the filtrate to obtain an aqueous phase and an organic phase, and extract the aqueous phase three times with ethyl acetate. Combine the organic phases, add anhydrous sodium sulfate to dry, filter, and rotary evaporation to remove the solvent. Then, distill the residue under reduced pressure to obtain a colorless transparent liquid, i.e., γ-selenobutyrolactone.
[0106] Step 4, preparation of selenolized carbon nanotubes:
[0107] In a 10 mL Schlenk tube equipped with a magnetic stirring bar, 0.40 mmol of γ-selenobutyrolactone, 0.3 mL of DMF and 0.40 mmol of amino carbon nanotubes were added. After stirring the reaction at 100 ° C for 10 minutes, the reaction mixture was cooled to room temperature and then dripped into 100 mL of methanol through a cotton filter. The obtained precipitate was filtered and dried in vacuum at 50 ° C to obtain selenol carbon nanotubes.
[0108] Step 5, preparation of selenolized carbon nanotube natural rubber:
[0109] 0.1 g of selenolated carbon nanotubes was added to 100 g of natural rubber solution with a solid content of 60 wt%, and 0.18 g of 10 wt% chlorine peroxide was added. After stirring for 1 hour under nitrogen protection, the dispersion was dried at 60°C to obtain selenolated carbon nanotube natural rubber.
[0110] Step 6, preparation of selenolized carbon nanotube natural rubber composite material:
[0111] 100 g of selenolized carbon nanotube natural rubber was placed in an open mill, 6 g of ZnO, 3 g of sulfur, 1 g of accelerator CZ and 80 g of carbon black were added, mixed at 140° C. for 0.5 h, placed in a flat vulcanizer, and kept at a constant temperature of 150° C. for 60 min to obtain a selenolized carbon nanotube natural rubber composite material.
[0112] Comparative Example 1
[0113] A method for preparing a natural rubber composite material comprises the following steps:
[0114] 100g of natural rubber was placed in an open mill, 5g of ZnO, 3g of sulfur, 1g of accelerator CZ and 50g of carbon black were added, mixed at 140°C for 0.5h, placed in a flat vulcanizer, and kept at a constant temperature of 150°C for 30min to obtain a natural rubber composite material.
[0115] Comparative Example 2
[0116] A method for preparing an amination-modified carbon nanotube natural rubber composite material comprises the following steps:
[0117] Step 1, preparation of carboxylated carbon nanotubes:
[0118] 1.00 g of CNTs was weighed and dispersed in a mixture of 20 mL of concentrated sulfuric acid and 20 mL of concentrated nitric acid, ultrasonically dispersed for 30 min, and then subjected to thermal reflux reaction at 140 ° C for 60 min. The product was washed with distilled water several times until neutral, filtered, and dried to obtain hydroxylated carbon nanotubes, recorded as CNTs-OH.
[0119] 50 mg of CNTs-OH was weighed and placed in 40 mL of DMF solvent, and ultrasonic dispersion was performed at an ultrasonic frequency of 100 Hz for 30 min to obtain a uniformly dispersed CNTs-OH suspension.
[0120] 0.2 g DCC, 0.015 g DMAP and 0.75 g acrylic acid were weighed and dissolved in 40 mL DMF solvent, then added to the CNTs-OH suspension and reacted at 85°C for 24 h under inert atmosphere. After washing, filtering and drying, carboxylated carbon nanotubes were obtained, which were recorded as CNTs-COOH.
[0121] Step 2, preparation of amino-modified carbon nanotubes:
[0122] CNTs-COOH, SOCl2, and DMF were mixed in a ratio of 200 mg: 20 mL: 1 mL, ultrasonicated at 50 ° C for 2 h, and then magnetically stirred at 70 ° C for 12 h. After the reaction, the system was heated to 120 ° C, most of the SOCl2 was evaporated, vacuum dried, and then added to excess ethylenediamine, where the mass ratio of CNTs-COOH to ethylenediamine was 200 mg: 0.06 mg. Then heated and stirred in an oil bath at 120 ° C for 24 h, cooled, filtered under reduced pressure with medium-speed qualitative filter paper, washed with anhydrous ethanol 5 to 8 times, and the product was vacuum dried at 50 ° C to obtain amino carbon nanotubes.
[0123] Step 3, preparation of amination carbon nanotube natural rubber:
[0124] 0.06 g of amino carbon nanotubes was added to 100 g of natural rubber solution with a solid content of 60 wt %, and after stirring for 0.6 h under nitrogen protection, the dispersion was dried at 60° C. to obtain amino carbon nanotube natural rubber.
[0125] Step 4, preparation of amination carbon nanotube natural rubber composite material:
[0126] 100g of amino carbon nanotube natural rubber was placed in an open mill, 5g of ZnO, 3g of sulfur, 1g of accelerator CZ and 50g of carbon black were added, mixed at 140°C for 0.5h, placed in a flat vulcanizer, and kept at a constant temperature of 150°C for 30min to obtain an amino carbon nanotube natural rubber composite material.
[0127] In the above embodiment of the present invention, the natural rubber contained in the natural rubber glue is mainly composed of isoprene, and its molecular chain contains a large number of unsaturated double bonds. In the above embodiment of the present invention, the carbon nanotubes are selenolized and modified so that the modified selenolized carbon nanotubes can react with the double bonds in the natural rubber, thereby making the selenolized carbon nanotubes more evenly dispersed in the natural rubber, achieving a better reinforcement effect.
[0128] The specific reaction principle is: first, selenol reacts with an oxidant to generate selenic acid, and then selenic acid reacts with an olefin to generate a selenoether compound. This reaction usually needs to be carried out in an inert atmosphere to avoid the decomposition of the oxidant or the oxidation of selenol. Therefore, after the carbon nanotubes are selenolized, the selenol groups will react with the double bonds in the natural rubber, so that the modified selenolized carbon nanotubes are evenly grafted on the natural rubber without agglomeration. Since double bonds exist in large quantities on the main chain of natural rubber, the selenolized carbon nanotubes modified in this way are mainly grafted with the main chain of natural rubber, and the distribution is more reasonable and stable.
[0129] Aminated carbon nanotubes are evenly distributed in natural rubber through covalent bonding or supramolecular methods. Among them, the covalent bonding method, such as the amide coupling method, has complicated steps; while the supramolecular method, such as hydrogen bonding or π-π stacking, has a weaker dispersion effect than selenolized carbon nanotubes. This is also confirmed by scanning electron microscopy tests.
[0130] The selenolized carbon nanotube natural rubber composite material prepared in the above embodiment is subjected to relevant test and analysis.
[0131] Test 1: Scanning electron microscopy analysis.
[0132] The selenolized carbon nanotube natural rubber composite material prepared in Example 1 was analyzed by scanning electron microscopy. Figure 1 to Figure 3 .
[0133] The amino carbon nanotube natural rubber composite material prepared in Comparative Example 2 was analyzed by scanning electron microscopy. Figure 4 .
[0134] pass Figure 1 to Figure 3 The scanning electron microscopy results show that after selenol modification, carbon nanotubes can be more evenly dispersed in natural rubber without agglomeration.
[0135] Similarly, in the scanning electron microscope analysis of the selenolized carbon nanotube natural rubber composite materials prepared in Examples 2 to 4, no agglomeration phenomenon was observed.
[0136] This shows that the selenol modification of carbon nanotubes helps to evenly disperse the modified selenol carbon nanotubes in natural rubber, thus solving the dispersion problem of carbon nanotubes and natural rubber.
[0137] pass Figure 4 The results of scanning electron microscopy show that the amino-modified carbon nanotubes are aggregated in natural rubber and are not evenly dispersed.
[0138] Test 2: Mechanical properties test.
[0139] Use AI-7000-M electronic tensile testing machine and test according to GB / T528-2009.
[0140] Mechanical properties of the selenolized carbon nanotube natural rubber composites prepared in Examples 1 to 4, the natural rubber composites prepared in Comparative Example 1, and the amination carbon nanotube natural rubber composites prepared in Comparative Example 2 were tested. The raw material input conditions are shown in Tables 1 and 2, and the test results are shown in Table 3.
[0141] Table 1 Raw material feeding conditions of each embodiment
[0142] Selenolized carbon nanotubes natural rubber ZnO sulfur Accelerator CZ Carbon Black Example 1 100g 5g 3g 1g 50g Example 2 100g 5g 3g 1g 40g Example 3 100g 4g 2g 1g 30g Example 4 100g 6g 3g 1g 80g
[0143] Table 2 Raw material feeding conditions of each comparative example
[0144]
[0145] Table 3 Mechanical properties test results
[0146]
[0147] By analyzing the results in Table 3, it can be seen that the 300% elongation stress and 500% elongation stress of Examples 1 to 4 are significantly higher than those of Comparative Examples 1 and 2. The tensile strength and Young's modulus of Examples 1 to 4 are also higher than those of Comparative Examples 1 and 2. This shows that selenolized carbon nanotubes have enhanced the mechanical properties of natural rubber.
[0148] Compared with Comparative Example 1, in Examples 1 to 4, when the amount of selenolated carbon nanotubes is the same and the amount of carbon black is different, as the amount of carbon black increases, the mechanical properties of the selenolated carbon nanotube natural rubber composite material are slightly improved, but not as much as the improvement when the amount of selenolated carbon nanotubes is increased.
[0149] Compared with Comparative Example 2, Examples 1 to 4 have lower dispersibility of amino carbon nanotubes in natural rubber than selenol carbon nanotubes. Therefore, in terms of mechanical properties, the improvement of natural rubber by amino carbon nanotubes is relatively poor compared with the improvement of natural rubber by selenol carbon nanotubes.
[0150] From the above analysis, it can be seen that in the embodiment of the present invention, selenolized carbon nanotubes are prepared by selenolating carbon nanotubes, and the selenolized carbon nanotubes are dispersed in natural rubber, which can play a good reinforcing role on natural rubber.
[0151] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a selenolized carbon nanotube natural rubber composite material, characterized in that: The following steps are involved: The aminated carbon nanotubes and the selenium-containing aliphatic heterocycles are subjected to a selenolation reaction, and the aminated carbon nanotubes are subjected to selenolation modification by the selenium-containing aliphatic heterocycles to prepare selenolated carbon nanotubes; the selenium-containing aliphatic heterocycles are γ-selenobutyrolactone; Under a protective atmosphere, the selenolated carbon nanotubes and natural rubber solution are reacted under the action of an oxidant to prepare selenolated carbon nanotube natural rubber; The selenol carbon nanotube natural rubber is mixed with a crosslinking agent, an accelerator and a reinforcing filler and vulcanized to prepare a selenol carbon nanotube natural rubber composite material.
2. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 1, characterized in that: The molar ratio of the amino carbon nanotubes to the selenium-containing aliphatic heterocycle is 0.02-0.4:0.02-0.
4.
3. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 1, characterized in that: The amino carbon nanotubes are prepared by the following method: The carboxylated carbon nanotubes are subjected to amination modification under the action of an acyl chloride reagent and an amination reagent to prepare the amination carbon nanotubes; the acyl chloride reagent is thionyl chloride; the amination reagent is ethylenediamine.
4. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 3, characterized in that: The amino carbon nanotubes are prepared by the following method: The carboxylated carbon nanotubes, acyl chloride reagent and organic solvent are mixed, stirred and reacted at 50°C to 70°C. After the reaction is completed, the acyl chloride reagent is evaporated to remove the acyl chloride reagent, and then an amination reagent is added, stirred and refluxed to prepare the amination carbon nanotubes.
5. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 4, characterized in that: The usage ratio of the carboxylated carbon nanotubes, the acyl chloride reagent, and the amination reagent is 200 mg: 20 mL: 0.06 mg.
6. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 1, characterized in that: The solid content of the natural rubber glue is 60wt%; the mass ratio of the selenolized carbon nanotubes to the natural rubber glue is 0.05-0.1:
100.
7. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 1, characterized in that: The oxidant is a hydrogen peroxide solution or a chlorine peroxide solution; the mass ratio of the natural rubber glue to the oxidant is 100:0.09-0.24; the mass percentage of the oxidant is 10wt%.
8. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 1, characterized in that: The crosslinking agent is sulfur; the accelerators are zinc oxide and N-cyclohexyl-2-benzothiazole sulfenamide; the reinforcing filler is carbon black; The mass ratio of zinc oxide to N-cyclohexyl-2-benzothiazole sulfenamide is 4 to 6:1; The mass ratio of selenolized carbon nanotube natural rubber, crosslinking agent, accelerator and reinforcing filler is 100:2-3:5-7:30-80.
9. The method for preparing the selenolized carbon nanotube natural rubber composite material according to claim 1, characterized in that: The mixing temperature is 130-150°C; the vulcanization temperature is 150°C; and the vulcanization time is 20min-60min.
Citation Information
Patent Citations
High-performance natural rubber vulcanized rubber of carbon-containing nano-tube, and preparation method thereof
CN101831090A
Method for preparing MOPPV-ZnSe-SWNTs (single-walled carbon nanotubes) composite material system
CN103467928A